1996
DOI: 10.1016/s0960-9822(02)70685-4
|View full text |Cite
|
Sign up to set email alerts
|

hMutSβ, a heterodimer of hMSH2 and hMSH3, binds to insertion/deletion loops in DNA

Abstract: In human cells, mismatch recognition is mediated by a heterodimeric complex, hMutSalpha, comprised of two members of the MutS homolog (MSH) family of proteins, hMSH2 and GTBP [1,2]. Correspondingly, tumour-derived cell lines defective in hMSH2 and GTBP have a mutator phenotype [3,4], and extracts prepared from these cells lack mismatch-binding activity [1]. However, although hMSH2 mutant cell lines showed considerable microsatellite instability in tracts of mononucleotide and dinucleotide repeats [4,5], only m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
248
1
1

Year Published

1997
1997
2000
2000

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 336 publications
(264 citation statements)
references
References 19 publications
14
248
1
1
Order By: Relevance
“…Instead, we found that aneuploidy was significantly correlated with hMSH3 frameshifts. Although a larger series of MSI aneuploid tumors must be analyzed before reaching a definitive conclusions on this point, these results suggest a possible role for hMSH3 in the maintenance of both microsatellite (Palombo et al, 1996) and chromosomal stability.…”
Section: Discussionmentioning
confidence: 90%
“…Instead, we found that aneuploidy was significantly correlated with hMSH3 frameshifts. Although a larger series of MSI aneuploid tumors must be analyzed before reaching a definitive conclusions on this point, these results suggest a possible role for hMSH3 in the maintenance of both microsatellite (Palombo et al, 1996) and chromosomal stability.…”
Section: Discussionmentioning
confidence: 90%
“…1), while hPMS1 and hPMS2 were found mostly in the insoluble fraction (data not shown). We argued that this could be due to incorrect folding of the PMS proteins in the absence of their cognate partner, similar to the case of the MutS homologues (13). The Sf9 cultures were therefore co-infected with all the possible combinations of the three baculovirus constructs.…”
Section: Expression Of Recombinant Mutl Homologues In Insectmentioning
confidence: 99%
“…This hypothesis was substantiated when germline mutations in the hMSH2 and hMLH1 genes, which encode the human homologues of the Escherichia coli MMR proteins MutS and MutL, were identified in HNPCC families (6 -9). Because mutations in these two genes accounted initially for only about one half of the HNPCC kindreds (10,11), and because biochemical (12)(13)(14)(15) and genetic evidence (1, 16 -18) demonstrated that both hMSH2 and hMLH1 proteins interact with other polypeptides in vivo, an intensive search was instigated for other genes that might function in MMR. To date, six MutS homologues (hMSH1-6) and several MutL homologues (hMLH1, hPMS1, and hPMS2, as well as a cluster of PMS-like (pseudo)genes on chromosome 7) have been identified in the human genome (19).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…MutS␣ (a heterodimer of MSH2 and MSH6) and MutL␣ (a heterodimer of MLH1 and PMS2) were isolated by virtue of their ability to restore strand-specific mismatch correction to nuclear extracts of repair-deficient tumor cell lines (16,18,30). In addition to its subunit function in MutS␣, MSH2 forms a molecular complex with the MutS homolog MSH3 (31,32). This MutS␤ complex binds to insertion/deletion mismatches and presumably plays a role in their processing.…”
mentioning
confidence: 99%